(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Breast cancer is among the most commonly diagnosed malignancies in women and remains difficult to treat due to therapy resistance and the adverse effects associated with conventional chemotherapeutic regimens. Mitragyna parvifolia is an Indian medicinal plant, which contains various phytochemicals including alkaloids, terpenoids, pteropodine, speciophylline and steroids. In the present study, we analysed the efficiency of phytochemicals, especially alkaloids from M. parvifolia using a network pharmacology and molecular docking approach. The phytochemicals were obtained from IMPPAT and the Coconut database. SwissADME, and ProTox 3.0 web servers were used to estimate the physicochemical, pharmacokinetic and toxicological profiles. Drug-likeness scores were obtained using OSIRIS Property Explorer. The network pharmacology and enrichment analyses predicted the potential targets which are extremely active against breast cancer, which include EGFR, ERBB2, AKT1 and PIK3CA. Molecular docking study against the chosen targets were performed using PyRx and interactions were visualised using Discovery Studio visualiser. Owing to the various in silico studies and drug score, the compounds, namely, Corynan-17-ol, Isomitraphylline and Isopteropodine were highly active against these targets with good binding energies and interaction profiles. Thus, these compounds may be used against breast cancer. However, further in vitro and in vivo studies are warranted to elucidate the exact mechanism of action of these compounds against breast cancer.